Alliance models among value chain participants in foreign markets: A focus on Korean LSPs - Hunsoo Lee (Asian Journal of Shipping and Logistics (AJSL), 2021)
This paper develops conceptual value chain alliance models through literature review and case studies. And it analyzes economic, industrial and logistics environments of Vietnam, Indonesia, Thailand, Myanmar and Ghana. Then the structure, flow and partnership of VC and SC and willingness to participate in the alliance of manufacturers, distributors and logistics firms in those countries are analyzed, through literature review, questionnaire analysis, site visits, interviews and case studies. Based on such analyses, the business models and strategies for global alliance among VC participants including manufacturers, distributors, LLPs and logistics SMEs are developed.
Keywords: 650; Alliance model; Value Chain; Global supply chain; Korean LSPs; SE Asia; Ghana